Infant Sleeping Environment in South-Eastern Nigeria (Sleeping Place and Sleeping Position): A Preliminary Survey - Ngozi S. Ibeziako; Roland Chidi Ibekwe; Bede C. Ibe (Journal of Tropical Medicine)
Objective. To determine infant sleeping position/place and the factors associated with them in South-eastern Nigeria. Methods. this is a cross-sectional study on infant sleeping environment. Subjects were the mother/ infant pairs that attended the well baby clinics at the Institute of Child Health of the University of Nigeria Teaching Hospital, Enugu (ICH-UNTH), Mother of Christ Specialist Hospital (MCSH), Enugu and the Ebonyi State University Teaching Hospital (EBSUTH), Abakaliki. Results. Lying on the side was the most common (51.1%) and the least stable sleeping position. Only 36.6% of infants who slept in that position were likely to be found in the same position the following morning; lying supine was the most stable (74.1%). The difference in stability of sleeping positions was statistically significant (𝑃<.01). Twenty six point seven percent of the mothers routinely lay their infants in prone position. On logistic regression, maternal parity was the only factor that was predictive of nonprone sleeping position (𝑃=.01). Bed sharing, though common (66.9%), was more among the experienced (𝑃=.03) and less educated mothers (𝑃<.01). Conclusion. There is a high level of prone sleeping position and bed sharing among infants in this study site. The potential consequences of these are unclear. There is therefore a need to conduct local studies to clarify its implication.